(untitled) (Observatorio Económico, 2011)
The government’s announcement that it will sell its shares in the water and sanitation utilities opens an ideological debate: the various explanations given to the public only call into question its role as an investor in firms whose control has long been in the hands of private owners. We face a long-standing debate about whether the State has any role as an entrepreneur —or, in this case, as an investor— in markets where the private sector can operate perfectly well. Continue reading...